A timely review of a key aspect of motor imagery: a commentary on Guillot et al. (2012) - Smith, Dave; Wakefield, Caroline (Frontiers in Human Neuroscience, 2013)
The timing of motor imagery has recently received attention from a number of researchers, culminating in a comprehensive review by Guillot and colleagues. This paper aims to further explore this issue, building upon the said review to suggest a number of other important timing-related issues. Specifically, we consider the possible role of bio-informational theory (Lang, 1979, 1985) and the recent proposal of ‘behavioural matching’ in conjunction with the PETTLEP model (Holmes & Collins, 2001) of motor imagery. Furthermore, we explore the possibility that timing has important implications for motivational aspects of imagery and the potential role of rhythm, an important but important but often overlooked aspect of skilled motor performance, and its links to the timing issue. We conclude by offering suggestions for future research to examine this relatively under-researched area of imagery.